2018
DOI: 10.1002/chem.201801712
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cation π‐Dimers of Conjugated Oligomers as Molecular Wires: An Analysis Based on Nitronyl Nitroxide Spin Labels

Abstract: Nitronyl nitroxide (NN)-substituted conjugated oligomers, which were expected to self-associate in biradical cation states, were designed to analyze the capability of π-dimers as molecular wires. The oligomer moieties were composed of dithienyl-N-methylpyrrole with methoxy substituents at the inner β-position of thiophene rings (DTP-NN ) and its propylenedioxythiophene (ProDOT) inserted derivative (DTP-P-NN ), or two ethylenedioxythiophene (EDOT) and two ProDOT units (E P -NN ). Among them, chemical one-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 74 publications
(183 reference statements)
1
12
0
Order By: Relevance
“…The new EPR line appeared during addition of AgSbF 6 along with MeSTh 2 DTP‐Ph‐NN (5 line) but the spectra are not resolved, as demonstrated in Figure S8d. The π‐dimerization of dithienylpyrrole radical cation molecules is known from the literature . Further addition of one more equivalent of the AgSbF 6 , kept at −10 °C for 6 h, five‐line EPR spectra were retained for Ph 2 DTP‐Ph‐NN and MeSTh 2 DTP‐Ph‐NN , the spectra for which are given in Figure S8e,f.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The new EPR line appeared during addition of AgSbF 6 along with MeSTh 2 DTP‐Ph‐NN (5 line) but the spectra are not resolved, as demonstrated in Figure S8d. The π‐dimerization of dithienylpyrrole radical cation molecules is known from the literature . Further addition of one more equivalent of the AgSbF 6 , kept at −10 °C for 6 h, five‐line EPR spectra were retained for Ph 2 DTP‐Ph‐NN and MeSTh 2 DTP‐Ph‐NN , the spectra for which are given in Figure S8e,f.…”
Section: Resultsmentioning
confidence: 96%
“…The p-dimerization of dithienylpyrrole radical cation molecules is known from the literature. [13,22] Further addition of one more equivalent of the AgSbF 6 ,k ept at À10 8Cf or 6h,f ive-line EPR spectra were retained for Ph 2 DTP-Ph-NN and MeSTh 2 DTP-Ph-NN,t he spectra for which are given in FigureS8e,f. These results indicate the dicationf ormation on the DTP core without decompositionoft he NN radical.…”
Section: Epr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of 1 2+ and 2 2+ , the VT measurements showed quite similar changes upon lowering the temperature as shown in Figure A,B, indicating that the similar π‐dimerization took place. These results suggested that supramolecular wires based on π‐dimerization between dication diradicaloids in a slipped stack manner were formed at the lower temperatures. Unfortunately, no farther evidence could not be obtained for the formation of supramolecular polymer, partly because the π‐dimerization was observed only at low temperatures in solution phase.…”
Section: Resultsmentioning
confidence: 89%
“…5 3,4-Ethylenedioxythiophene 7 and 4,5-ethylenedioxytetrathiafulvalene 8 have been investigated to obtain widely applicable donor molecules, because ethylenedioxy-substituted donors are endowed with enhanced donor ability, stability of radical cations, and moderate solubility in common organic solvents. In the course of our studies on ethylenedioxy-substituted molecules, [9][10][11] we are interested in the synthesis and donor properties of tris(ethylenedioxy)benzene (3) and bis(ethylenedioxy)thiophene (4) (Figure 1). Here, we report an improved synthesis of 3 by using cyclotrimerization of organotin molecules in a one-pot procedure as well as the first synthesis of 4 with insertion of sulfur to 1,4-dilithio-1,3-butadiene unit.…”
Section: Introductionmentioning
confidence: 99%